Soil and Plant Tissue Testing - Maria L. Silveira (EDIS)
Soil testing is the best tool for monitoring soil fertility levels and providing baseline information for cost-effective fertilization programs. But a major limitation is that it typically accounts for the plant-available nutrient pool present in the surface soil layer. Because of the extensive root system in some plants, plant analysis is a complement to the soil test to better assess the overall nutrient status of a perennial forage system, while revealing imbalances among nutrients that may affect crop production. This 4-page fact sheet was written by Maria L. Silveira and published by the UF Department of Soil and Water Science, June 2014.